Fac-to-mer isomerization triggers hydride transfer from Mn(i) complex fac-[(dppm)Mn(CO)3H]. Issue 32 (4th April 2022) - Osipova, Elena S.; Gulyaeva, Ekaterina S.; Kireev, Nikolay V.; Kovalenko, Sergey A.; Bijani, Christian; Canac, Yves; Valyaev, Dmitry A.; Filippov, Oleg A.; Belkova, Natalia V.; Shubina, Elena S.
Abstract : Spectroscopic and theoretical studies revealed the crucial role of elusive Mn(i ) meridional species in hydride transfer being potentially relevant for Mn-catalyzed hydrogenation-type processes. Abstract : Low-temperature IR and NMR studies combined with DFT calculations revealed the mechanistic complexity of apparently simple reactions between Mn(i ) complex fac -[(dppm)Mn(CO)3 H] and Lewis acids (LA = Ph3 C +, B(C6 F5 )3 ) involving the formation of so-far elusive meridional hydride species mer -[(dppm)Mn(CO)3 H⋯LA] and unusual dearomatization of the Ph3 C + cation upon hydride transfer.